2018
DOI: 10.1213/xaa.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Erector Spinae Plane Catheter for Analgesia After Infant Thoracotomy: A Case Report

Abstract: The erector spinae plane block is an emerging technique for the provision of thoracolumbar analgesia with reported pediatric applications. We describe the placement of a continuous erector spinae plane catheter at the T5-T6 level in a 7-month-old infant who was undergoing thoracotomy for left upper lobectomy due to congenital pulmonary airway malformation. This technique resulted in outstanding analgesia without the need for opioid rescue analgesia. This block has a low degree of technical difficulty and is pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…After reviewing the literature regarding ESPBs in children, we found 33 publications as of May 2019 (see Table ) . These included 28 different case reports (three or less patients), three case series (greater than three patients), and two randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the literature regarding ESPBs in children, we found 33 publications as of May 2019 (see Table ) . These included 28 different case reports (three or less patients), three case series (greater than three patients), and two randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the ESP block is limited to the thoracic region in the pediatric population, with only a few reports (Table 1). It has been reported to provide effective postoperative analgesia for thoracic surgeries [610], nephrectomy [11], inguinal hernia repair [12], and laparoscopic cholecystectomy operations [13] in children. To our knowledge, ESP block performed in the lumbar region has not been reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that they were able to achieve adequate anesthetic spread and analgesia with a volume of 0.2–0.3 ml/kg in other pediatric patients undergoing thoracic surgery. Kaplan et al [10] reported the successful use of a modest amount of local anesthetic with an approximately 0.3 ml/kg bolus in an infant weighing 7 kg. Future studies on the optimal local anesthetic volume and concentration when performing ESP block in children would be useful to practitioners and to further enhance the understanding of this useful block.…”
Section: Discussionmentioning
confidence: 99%
“…El bloqueo del ESP es una técnica recientemente descrita en pacientes adultos y para manejo de dolor neuropático, según mencionado por los autores (5). Actualmente el bloqueo ESP se viene realizando en la población pediátrica, con solo pocos informes (Tabla I), para manejo del dolor postoperatorio de cirugías torácicas (11)(12)(13)(14)(15)(16)(17), nefrectomía (18), reparación de hernia inguinal (19), colecistectomía laparoscópica (20), displasia de cadera (21) e hipospadias (22). Hasta donde sabemos, el bloqueo ESP para dolor neuropático en niños aún no se ha reportado.…”
Section: Discussionunclassified